Dzis do ciebie przyjsc nie moge...;
Seite 1:<NZ>1. Przysiega (The oath)<NZ>2. Dzis do ciebie przyjsc nie moge (I can't come to you today)<NZ>3. Pierwszy czlowiek (First man)<NZ>4. A jesli bedzie wiosna (And should the spring come)<NZ>5. Zrzut przyjmujemy dzis albo juz nigdy... (We will receive the air-drop today, or else never)<NZ>6. Natalia (Natalie)<NZ>7. Warta (Sentry)<NZ>8. Asturia (Asturia)<NZ>9. Listy (Letters)<NZ>10. My ze spalonych wsi (We come from the burned villages)<NZ><NZ>Seite 2:<NZ>1. Szturmówka (Song of the attach)<NZ>2. Czekam Cie... (I wait for you)<NZ>3. Dobij mnie (Give me the blow of mercy)<NZ>4. Smutna rzeka (Sad river)<NZ>5. Pogrzeb (Funeral)<NZ>6. Wo sind die Banditen? (Where are the bandits?)<NZ>7. Hej, chlopcy (C'mon, boys)<NZ>8. Moja mala (My little girl)<NZ><NZ>Seite 3:<NZ>1. Ballada o Jastrzebiu (Ballad about the hawk)<NZ>2. Serce w plecaku (A spare heart in knapsack)<NZ>3. Matka (Mother)<NZ>4. Marsz Mokotowa (Mokotów March)<NZ><NZ>Seite 4:<NZ>1. Wigilia (Christams Eve)<NZ>2. Zaglada Oddzialu (Extermination of a fighting unit)<NZ>3. Czerwone maki na Monte Cassino (Red poppies on Monte Cassino)<NZ>4. Oka (The Oka river)<NZ>5. Final (Finale);